2017
DOI: 10.1177/1758834017742627
|View full text |Cite
|
Sign up to set email alerts
|

Personalization of regorafenib treatment in metastatic gastrointestinal stromal tumours in real-life clinical practice

Abstract: Background:Regorafenib (REG) has now been approved as the standard third-line therapy in metastatic gastrointestinal stromal tumour (GIST) patients at the recommended dose and schedule of 160 mg once daily for the first 3 weeks of each 4-week cycle. However, it has a relevant toxicity profile that mainly occurs within the first cycles of therapy, and dose and schedule adjustments are often required to reduce the frequency or severity of adverse events and to avoid early treatment discontinuation. To date, larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 19 publications
(38 reference statements)
1
14
0
Order By: Relevance
“…Even though regorafenib represents an effective treatment option for patients with metastatic GIST, its recommended schedule (160 mg daily, 3-weeks-on, 1-week-off) has the major drawback of unsatisfactory patient adherence due to relevant, sometimes hardly bearable, treatment-related AEs. 19 , 20 , 21 , 22 , 23 In order to tackle this issue, physicians usually adopt various dosing and schedules of regorafenib, in order to optimize treatment and avoid early discontinuation. 16 , 18 , 20 However, to the best of our knowledge, no data on the impact of regorafenib-personalized schedules on therapeutic outcomes in patients with advanced GIST have been published.…”
Section: Discussionmentioning
confidence: 99%
“…Even though regorafenib represents an effective treatment option for patients with metastatic GIST, its recommended schedule (160 mg daily, 3-weeks-on, 1-week-off) has the major drawback of unsatisfactory patient adherence due to relevant, sometimes hardly bearable, treatment-related AEs. 19 , 20 , 21 , 22 , 23 In order to tackle this issue, physicians usually adopt various dosing and schedules of regorafenib, in order to optimize treatment and avoid early discontinuation. 16 , 18 , 20 However, to the best of our knowledge, no data on the impact of regorafenib-personalized schedules on therapeutic outcomes in patients with advanced GIST have been published.…”
Section: Discussionmentioning
confidence: 99%
“…A German study by Mross et al , revealed that REG presented similar pharmacokinetic and pharmacodynamic effects for dose levels from 120 to 220 mg; moreover, no significant pharmacologic activity was shown at doses of less than 120 mg. 35 As regards current clinical practice, the use of REG seems heterogeneous, with several authors which recommend REG at the starting dose of 80 or 120 mg and subsequent dose-escalation, and others which prefer shorter cycles at standard doses of 160 mg. 36 , 37 In our recent retrospective Italian multicentre experience, we identified approximately 20 different strategies of treatment personalization in patients affected by advanced or metastatic GIST, including dose reduction from 160 to 120 mg, 120 mg as starting dose, the initial dose of 80 mg and several others. 38 Of note, whatever was the strategy adopted, REG treatment personalization has led not only to a clinical benefit defined as complete or partial resolution of side effects in almost all patients, but especially positively affected the duration of REG treatment. In particular, a median duration of 9.9 months was observed, significantly greater than the 22.9 weeks of the GRID trial, with 23% of patients who exceeded 20 months and a mean duration of 32.14 months (range 20.50–53.67 months).…”
Section: Discussionmentioning
confidence: 99%
“…[ 13 ] In addition, in regorafenib treatment for gastrointestinal stromal tumor and colorectal cancer, treatment could be continued while suppressing the relapse or exacerbation of adverse events by dose reduction or a change in the administration schedule based on the adverse events occurring during prior treatment. [ 14 , 15 ] This suggested that reductions in the starting dose of regorafenib based on the clinical characteristics of patients with advanced HCC improved their prognosis. We utilized the liver function and adverse events during sorafenib treatment as the deciding criteria in patients to determine the starting dose of regorafenib.…”
Section: Discussionmentioning
confidence: 99%